A COMPARATIVE ANALYSIS OF SENTENCE STRUCTURE IN KOREAN AND ENGLISH - Mamatqosimova Mashhura (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
In modern linguistics, the comparative study of syntactic structures across languages is considered one of the key research areas. In particular, analyzing languages that belong to different language families provides valuable insights into both similarities and differences in grammatical systems. Korean and English are suitable subjects for such analysis, as they differ significantly in terms of sentence structure. English belongs to the Indo-European language family and is characterized as an analytic language, whereas Korean is an agglutinative language. These typological differences lead to substantial variation in their syntactic organization. The aim of this study is to identify and comparatively analyze the main features of sentence structure in Korean and English.